Enhancement of dissolution of atorvastatin through preparation of polymeric solid dispersions using supercritical fluid technology - Bashar Altaani; Rana Obaidat; Walaa Malkawi (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: This study aimed at preparation of solid dispersions in order to enhance dissolution of poorly water-soluble atorvastatin using supercritical CO2 technology. Atorvastatin has poor bioavailability of 12%, mainly due to poor water solubility and dissolution. Dispersion of drugs in various hydrophilic carriers using supercritical fluid technology has been found to be an outstanding method to prepare solid dispersion. Experimental approach: Four different polymers were employed. These were polyvinyl pyrrolidone K30 (PVP), polyethylene glycol 6000 (PEG), Soluplus® and chitosan. Full physicochemical characterizations were performed in addition to in vitro dissolution study. Findings / Results: The used polymers enhanced the dissolution rate of atorvastatin. However, supercritical parameters affected the dissolution profile and drug loading efficiency of the prepared dispersions. High performance liquid chromatography assay indicated the stability of the prepared PEG, Soluplus® andchitosan-based dispersions. On the other hand, PVP solid dispersions were not stable and formed sticky paste. Powder X-ray diffraction showed similar patterns for PEG-based dispersions after exposure to storage condition, while the intensity of atorvastatin peaks increased after three months of storage of Soluplus® and chitosan dispersions. Conclusion and implications: Supercritical fluid technology proved to have great potential to prepare dispersions for biopharmaceutics classification system (BCS) class II drugs. Dissolution enhancement of atorvastatin was achieved through successful preparation of polymeric dispersions of the drug using the supercritical technology without further addition of solvents.